Community-Based Digital Literacy in Cultural Tourism Promotion: A Case Study of The Muarajambi Temple Community on Social Media - Fatya Kariadna; Johannes Johannes; Logi Mulawarman (Lembaga Penelitian Universitas YARSI, 2026)
This study examines how communities in the Muarajambi Temple area develop and apply digital literacy in promoting cultural tourism through social media. Despite growing adoption of digital platforms, community promotional practices remain inconsistent and largely undirected. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation involving eight informants from six local communities. Analysis followed the interactive model of Miles and Huberman, with digital literacy assessed through the framework of Chodijah et al. (2022), encompassing internet searching, hypertextual navigation, content evaluation, and knowledge assembly. Findings reveal that community digital literacy has developed as a self-directed, adaptive, and experience-based collective practice. Communities utilize Instagram, TikTok, and websites through documentary, informative, and educational content patterns, yet face persistent challenges including inconsistent posting, limited devices, and the absence of strategic content planning. A critical gap was identified between stated practices and field observations, suggesting that interview statements partly reflect community aspirations rather than established behavioral routines. Strengthening community-based digital literacy through sustained training, internal accountability structures, and multi-stakeholder collaboration is key to building effective, innovative, and sustainable cultural tourism promotion